Transformação genética e análise da expressão gênica de clones de Eucalyptus spp sob déficit hídrico - Martins, Guilherme Silva (2015)
Aiming the comprehension of drought defenses mechanisms of Eucalyptus spp. and to obtain tolerant genotypes, this work evaluated, by RT-qPCR, the expression patterns of six genes EgrCPK26, EgrDREB2, EgrNCED3, EgrPYR1, EgrMET1 and EgrDDM1, in two Eucalyptus camaldulensis X Eucalyptus urophylla clones (VM01- drought tolerant and VM05 – drought susceptible) in drought and irrigation conditions. For the expression normalization, references genes was, firstly, used. Besides, this work aimed the development of an Eucalyptus grandis X Eucalyptus urophylla transgenic line with the gene OsCPK5 and evaluated the effect of its insertion in the expression of four genes related to drought response, EgrCPK26, EgrDREB2, EgrNCED3 e EgrPYR1.Primarily, the stability of seven candidates as reference genes (SAND, IDH, PP2A-3, PP2A-1, UBQ, TUB and EF- 1α) was evaluated through the geNorm, NormFinder, BestKeeper and Delta-Ct algorithms, in the two clones of E. camaldulensis X E. urophylla under drought and watered conditions. According to the data found, it was possible to verify a higher stability value of the genes SAND and PP2A-3 in the great part of the samples sets. In addition some studies suggest the normalization using three references genes, selecting the third gene more stable, EF-1α. In the second experiment, the expression of the genes EgrCPK26, EgrDREB2, EgrNCED3, EgrPYR1, EgrMET1 and EgrDDM1 was evaluated in the two clones (VM01 and VM05) in the same conditions tasted before. The reference genes used in the expression normalization was SAND, PP2A-3 and EF-1α. In meanwhile, the water potential of all the treatments was observed. When under drought conditions, the clone VM01 showed a higher expression of the EgrCPK26, EgrDREB2, EgrNCED3 and EgrPYR1then the clone VM05. Based on previous studies, these genes are related to many signaling and tolerance processes against drought, showing a higher expression in tolerant genotypes. These data are supported by the water potential values, which the VM05 presented a severe reduction in stress conditions, whilst the clone VM01 had a slight decrease. In the third experiment, a genetic transformation was done, through the Agrobacterium tumefaciens infection, aiming the insertion of the OsCPK5 gene in Eucalyptus grandis X Eucalyptus urophylla seedlings. Based on the PCR reactions, it was possible to obtain, successfully, fifteen transgenic lines. After the expression analysis of the EgrCPK26, EgrDREB2, EgrNCED3 and EgrPYR1, it was verified a difference in the transformed plants when compared with the wild type, showing an impact of the gene insertion through genetic transformation on the drought response of E. grandis X E. urophylla seedlings.